The Role of Public Accounting Firm Quality and Managerial Ownership on the Integrity of Financial Statements in Insurance Companies listed on the IDX - Desi Natalia Tampubolon; Fajar Syaiful Akbar (Journal of Economics, Business, and Government Challenges, 2021)
The intent of the discussion of the study this is to understand and prove empirically the “The influence of management ownership and the eff ect of the quality of the public accounting firm (KAP) on the Integrity of Financial Statements in insurance companies listed on the IDX”. The discussion of this study applies the “quantitative method”. The type of data applied in the discussion of this study is “secondary data”. The discussion of this study uses the object of research, namely, “insurance companies for the period 2015-2019” and the research subject is “Financial Statements and Independent Auditor Reports for the 2015-2019 period obtained from IDX”. The sampling technique used in the discussion of this study applies the purposive sampling method”. Researcher using “14 insurance companies listed on the Stock Exchange 2015-2019 period” with 5 years of observation, which means the total sample in this study discussion a linear regression analysis”, using SmartPLS 2.0.M3 software. The findings in the discussion of this study show how the “Influence of Managerial Ownership (X1) variable has been shown to have a negative and significant effect on the Integrity of Financial Statements (Y), and the Influence of Public Accounting Firm Quality (X2) variable has been shown to have positive and significant effect on the Integrity of Financial Statements (Y)”.